Pre-vocational Education in the Curriculum and Its Teaching Practice : A Study of Seven European Countries - Berger, Susanne [Verfasser]; Pilz, Matthias [Verfasser] (My University, 2012)
The article presents the findings of a comparative research project on pre-vocational education in lower secondary schools (ISCED Level 2) in seven European countries. The aim of the study was to better understand how the pre-vocational education curriculum is shaped and how the written syllabuses are interpreted and taught by individual teachers within schools. The countries covered are Austria, Germany, Hungary, Latvia, Poland, Portugal and Scotland. Two research methods have been used: First, the content analysis of the relevant syllabuses focused on how, and to what extent, pre-vocational education competencies are embedded in the official curriculum. Second, 75 teachers took part in qualitative expert interviews about their interpretation and implementation of the relevant curriculum. The findings of the study show that there is a distinct pre-vocational curriculum within each of the investigated countries. Furthermore, the prescribed curriculum is taught (or 'enacted') very differently within the schools. The differences in curriculum implementation can be explained, amongst other factors, by the availability of resources and the initial and further training of teachers. (BIBB-Doku)
Keywords: S 1.2 Berufsvorbereitung; G 1.3.2.2 Übergänge; T 1.5 International vergleichende Berufsbildungsforschung; I 2.1 Deutschland; I 2.2.2 Osteuropa; Berufsvorbereitung; Berufseinmündung; Curriculum; Sekundarbereich; Lehrer; Internationaler Vergleich; Bundesrepublik Deutschland; Österreich; Polen; Schottland; Ungarn; Portugal; Lettland